The facilitation of a team-building process: Implications for mental health - Antoinette Gmeiner; Sandra van Wyk (AOSIS, 2001)
The goal of this article was to explore and describe team members' experience of obstacles in their functioning as an effective team and their views of elements contributing to an effective and productive team. Opsomming Die doel van hierdie artikel was om spanlede se ervaring van struikelblokke in effektiewe spanfunksionering te verken en te beskryf, asook om hul menings ten opsigte van elemente wat kan bydra tot 'n effektiewe en produktiewe span in te win. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.